Ability in Mathematics Problem Solving Based On Adversity Quotient - Malik, Ibnu; Mulyono, Mulyono; Mariani, Scolastika (Jurnal Profesi Keguruan, 2019)
The objective of this research is to know mathematics problem-solving ability viewed from adversity quotient. The research method used in this research is qualitative research method. The population in this research is forty students of the eighth-grade students of SMP Negeri 1 Sumber, Cirebon, West Java, Indonesia. The sampling method used in this research is Purposive Sampling. Data gathering methods consist of test, observation, documentation, questionnaire, and interview. The research shows that quitter students group has not been able to perform all problem-solving steps, including understanding the problem, planning a problem solving, performing the problem solving, and reviewing the answer. Camper students group can perform 75% of the problem-solving steps; they understand the problem, planning a problem solving, performing the problem solving, but not in reviewing the answer. Climber students groups can perform 100% of the problem-solving steps; they understand the problem, planning a problem solving, performing the problem solving, and reviewing the answer.